Reactive flow and photon fate in a mesoscale reactor applied to the photocatalytic abatement of pollutants in gas phase: a theoretical investigation - Matiazzo, Tatiana (2022)
Tese (doutorado) - Universidade Federal de Santa Catarina, Centro Tecnológico, Programa de Pós-Graduação em Engenharia Química, Florianópolis, 2022.